2021
DOI: 10.1021/acs.chemmater.1c01201
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation System to Predict Missing Adsorption Properties of Nanoporous Materials

Abstract: Nanoporous materials (NPMs) selectively adsorb and concentrate gases into their pores, and thus could be used to store, capture, and sense many different gases. Modularly synthesized classes of NPMs, such as covalent organic frameworks (COFs), offer a large number of candidate structures for each adsorption task. A complete NPM-property table, containing measurements of the relevant adsorption properties in the candidate NPMs, would enable the matching of NPMs with adsorption tasks. However, in practice the NP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 110 publications
0
19
0
Order By: Relevance
“…Additionally, due to the capacities of interpolation and extrapolation, MOFNet can potentially be applied to missing data imputation of gas adsorption isotherms in databases. We found reports of related attempts, and our model may help to complete missing adsorption properties of nanoporous materials. In terms of the training data set, previous studies are mainly based on the hMOF data set, which has limited diversity in types of metal atoms and metallic corners.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, due to the capacities of interpolation and extrapolation, MOFNet can potentially be applied to missing data imputation of gas adsorption isotherms in databases. We found reports of related attempts, and our model may help to complete missing adsorption properties of nanoporous materials. In terms of the training data set, previous studies are mainly based on the hMOF data set, which has limited diversity in types of metal atoms and metallic corners.…”
Section: Discussionmentioning
confidence: 64%
“…As illustrated in Figure 2c, the latent vectors of COFs (M) and gas-adsorption properties (P) were directly learned through decomposing the COF-property matrix (A); after projecting the latent vectors of COFs onto a 2D space, the proximity between COFs and similar adsorption properties was observed, thus revealing the similarity across different COFs. 33 Model Training. Many ML studies for MOFs aim to establish structure−property relationships via supervised learning, generally known as regression or classification (Figure 1c).…”
Section: ■ Introductionmentioning
confidence: 99%
“…36 By projecting the latent vectors of COFs into a 2D space based on PCA, Sturluson et al observed similar adsorption properties in clustered COFs, hence suggesting the physical robustness of such data-driven latent vectors. 33 Despite being computationally efficient, PCA is subject to a linear assumption across different features and hence inherently falls short in capturing nonlinear relationships. As an improvement over PCA, the nonlinear manifold learning technique assumes that the original high-dimensional feature space can be approximately embedded by low-dimensional manifolds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…27,28 To learn the low-rank latent representation of the movies and users, MF needs a few example ratings; this requirement for a new movie or user is known as the "cold-start problem". 27 Matrix factorization approaches have been applied to a variety of chemical systems, e.g., to predict gas adsorption in nanoporous materials, 29,30 diffusion coefficients 31 and activity coefficients 32−35 of binary liquids, Henry's law coefficients, 36 the synthesis of metal oxides 37,38 and halide perovskites, 39 gas permeabilities in polymers, 40 and antiviral activities of molecules. 41 In these examples, the rows and columns represent different entities (e.g., gases and sorbents, elements, and reaction conditions) like the movie setting.…”
Section: ■ Introductionmentioning
confidence: 99%